2016
DOI: 10.1186/s40729-016-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of dental implant success rate in patients with AIDS

Abstract: BackgroundOral health care of patients with acquired immune deficiency syndrome (AIDS) due to human immunodeficiency virus (HIV) is a growing area of concern, taking into consideration the increased life expectancy of patients resulting from antiretroviral therapy. There is insufficient literature regarding the impact of dental implants in AIDS patients. This study investigated the long-term clinical outcome of implant placement in patients diagnosed with AIDS.MethodsThis monocentric study included AIDS patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…It has been reported that complications in bone mineral metabolism are often manifested in patients with CKD compared with individuals without CKD. [33][34][35] We hypothesize that soft-tissue inflammation and CBL are significantly higher around adjacent implants placed in type-2 diabetic patients with other systemic diseases than patients with type-2 diabetes alone. 32 Similarly, a higher CBL around dental implants has been reported in patients with AIDS, CVD, and liver diseases compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that complications in bone mineral metabolism are often manifested in patients with CKD compared with individuals without CKD. [33][34][35] We hypothesize that soft-tissue inflammation and CBL are significantly higher around adjacent implants placed in type-2 diabetic patients with other systemic diseases than patients with type-2 diabetes alone. 32 Similarly, a higher CBL around dental implants has been reported in patients with AIDS, CVD, and liver diseases compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic diseases such as AIDS and poorly‐controlled DM are prospect of peri‐implant diseases . Moreover, habitual use of smokeless tobacco products has also been associated with increased soft‐tissue inflammation and alveolar bone loss around natural teeth and dental implants .…”
Section: Discussionmentioning
confidence: 99%
“…In Systemic diseases such as AIDS and poorly-controlled DM are prospect of peri-implant diseases. 28,29 Moreover, habitual use of smokeless tobacco products has also been associated with increased soft-tissue inflammation and alveolar bone loss around natural teeth and dental implants. [30][31][32] In this presented study, stringent criteria for participants inclusion and for the exclusion were adopted such as patients with a history of ST product usage, and patients with immunosuppressed health statuses.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kanjevac et al complications in bone mineral metabolism are occasionally in patients with kidney diseases compared with individuals without kidney‐related disorders. Likewise, CBL around dental implants has been reported among tobacco‐smokers and patients with AIDS, CVD, and liver diseases compared with healthy nonsmoking controls . We therefore speculate that tissue inflammation and CBL are significantly higher around ADI placed in immunocompromised patients and tobacco‐smokers compared with systemically healthy never‐smokers.…”
Section: Discussionmentioning
confidence: 69%
“…33 The Ozgur study 33 and liver diseases compared with healthy nonsmoking controls. [35][36][37] We therefore speculate that tissue inflammation and CBL are significantly higher around ADI placed in immunocompromised patients and tobacco-smokers compared with systemically healthy never-smokers.…”
Section: Discussionmentioning
confidence: 85%